PENGARUH PENDIDIKAN AGAMA ISLAM TERHADAP MOTIVASI SHOLAT BERJAMAAH DI SEKOLAH MENENGAH ATAS 4 KOTA CIREBON - Asep - Kurniawan (Pendidikan Agama Islam, Fakultas Ilmu Tarbiyah dan Keguruann, IAIN Syekh Nurjati Cirebon, 2019)
So far the lessons of Islamic religion always emphasize concepts. It does not instill values and practices. Therefore, religious teachers must change learning models, which instill values and practice Islamic teachings in daily life, including the implementation of congregational prayers. The research aimed to reveal the extent of the influence of Islamic religious education on the motivation to pray in congregation at state senior high schools 4 Cirebon City. This research method was a quantitative descriptive correlation. The instrument was a questionnaire. This population was 156 respondents of class XIII of the Natural Sciences and Social Sciences. The data analysis technique was Chi-Square formula. Islamic education learning in class XIII in state senior high schools 4 Cirebon City is categorized as medium. This was indicated from the average value of 26.75. Similarly, the motivation to pray in the congregation of class XIII students at in state senior high schools 4 Cirebon City was categorized as medium. This could be seen from the average value of 22,575. There was a moderate influence of Islamic religious education on the students’ motivation of class XIII state senior high schools 4 Cirebon City to pray in congregation.